Universitäre Gerechtigkeit und Gesundheitsoutcomes - Diehl, Katharina; Deyerl, Veronika; Herr, Raphael (Public Health Forum, 2024)
Perceptions of stress and the prevalence of mental illness are growing concerns among students. One source of stress may be perceived injustice in the university environment. The underlying concept of organizational justice is associated with various mental and physical health outcomes among employees. The aim of the present project is to transfer this concept, which is well established in work stress research, to students.
CRIS-Team Scopus Importer:2024-06-07
Keywords: injustice; mental health; stress; students; University